Brilliant social media : how to start, refine and improve your social media business strategy - Gray, Adam (Business writer) (Brilliant., 2013)
FAZED BY FACEBOOK? TONGUE-TIED BY TWITTER? LOST ON LINKEDIN? LEARN HOW TO NAVIGATE THE SOCIAL MEDIA JUNGLE, AND FIND OUT HOW TO GET YOUR BUSINESS NOTICED. Social media is easy when you know how - this practical guide shows you how to get started, then refine and improve your strategy to get real business results. Many businesses know that social media is important - but they either haven't made a start or are dabbling without a proper strategy in place. It's easy to feel overwhelmed by the task - how much of my time will it take? When will I see the benefit? What do I do to get heard? How.